أثر التمكين الإداري على الرضا الوظيفي دراسة ميدانية على المصارف السورية - محسن بنان (Latakia University Journal - Economic and Legal Sciences Series, 2016)
تهدف هذه الدراسة إلى معرفة أثر التمكين الإداري في تحقيق الرضا الوظيفي لدى العاملين في المصارف السورية ولتحقيق أهداف الدراسة استُخدمت استبانه لجمع البيانات ووزعت على عينة بلغ حجمها 120 فرد وكان عدد الاستبانات الصالحة للتحليل 90 استبانة .وفي التحليل الإحصائي للبيانات تم اتباع عدة أساليب تضمنت المتوسط الحسابي والانحراف المعياري وتحليل الانحدار المتعدد .... الخ ، وقد توصلت الدراسة إلى نتائج تفيد أن متغيرات الدراسة المستقلة الخاصة بالتمكين الإداري (تدريب العاملين, تحفيز العاملين, فرق العمل , الاتصال الفعال) لها اثر على المتغير التابع الرضا الوظيفي بينما تفويض السلطة ليس له اثر ذو دلالة إحصائية This study aimed at exploring the effect of the empowerment in job satisfaction among workers at Syrian banks .To achieve the objectives of study a questionnaire was developed to collect data from the study sample, a total of 120 questionnaires were distributed of which 90 questionnaires were returned and were ready for analysis Data were analyzed using a number of statistical techniques including: the mean, standard deviationand Stepwise Multiple Regression, ..etc. it was found that the independent variables of empowerment (effective communication, motivation, training, and team work) affect the dependent variable (job satisfaction).While the delegation of authority does not have a statistically significant effect.